The effect of Momordica Carantia (Bitter Mellon) extracts on human Adenocarcinoma cells proliferation and apoptosis - Ahmad Sujangi, Nurhikmah; Jamil, Elyna Fatini; Abdul Ghani, Radiah (2021)
Abstract: Chemoprevention is a crucial process in overcoming the cancer burden throughout the world. By changing dietary choices, people who are at high risk of developing cancer may slow down the carcinogenesis or preventing it altogether. Some food contains high level of polyamine which is bad due to its ability for promoting tumor growth. Hence, this research aimed to determine the polyamine content of selected local plant, Momordica charantia by using High Performance Liquid Chromatographic (HPLC) analysis as well as conducting cytotoxicity study and growth inhibition study of the plant extracts against the human lung adenocarcinoma epithelial cell lines, A549. The type of cell death and its pathway also were elucidated. The polyamine content of M. charantia was found to be high (more than 200 nmol/g/mol). It is found to induce cytotoxicity against A549 cells after only 24 hours of exposure which lead to the establishment of the IC50 at 10.0 mg/ml. Growth curve analysis demonstrated that M. charantia had successfully reduced the cancer cell progression. On the other hand, there was an increase of intracellular polyamines in the treated cells compared to untreated cells. Apoptosis was induced Based on these preliminary findings, it can be concluded that M. charantia and G. procumbens are not an excellent plants to be included in the development of chemoprevention strategy as the ideal chemopreventive agents are those that contain low polyamine level, able to reduce the cancer cell progression and can inhibit the biosynthesis of polyamine in cancer cells to avoid recurrence of cancer. However, further investigation on the effect of these plants on polyamine metabolic pathway and cell death pathway shall be elucidated.